The factors that influence the malay community in the use of accommodation technology applications in kota bahru, kelantan. - Muhammad Hisham Buyong Surja; Muhammad Haiqal Solihin Mat Salleh; Muhammad Faries Khairul Hasni; Muhammad Firdaus Abdul Jalil (2022)
This study is about the factors that influence malay community in using accommodation applications in Kota Bharu, Kelantan. Youth are a vulnerable group with the various technologies and applications available today. Therefore, this research is focused on the young people in Kota Bharu, Kelantan. This research is to identify the ease of use in simple accommodation applications and behavioral intentions. Second, to examine whether the facilities provided in the accommodation application and behavioral intention. Finally, to examine the relationship between the security provided in the accommodation application and behavioral intention. Quantitative methods were chosen and used in this study in the form of a questionnaire. Total of 120 respondents who use accommodation application facilities in Kota Bharu, Kelantan, Malaysia were selected in this study and from that number, a total of ten people respondents were interviewed in depth. Keywords: Influence youngster, accommodation application